Kepemimpinan Diri Terhadap Komitmen Organisasional Pada Guru SMPN di Kota Bengkulu: Menguji Mediasi Kecerdasan Emosional - Rohman, A. Saipur; Pareke, Fahrudin JS (UMSU, 2024)
Organizational commitment plays a crucial role as highly committed individuals are expected to have the skills to manage internal emotions, especially when facing potential problems. Factors such as personal values, self-confidence, intrinsic motivation, personality, job satisfaction, and emotional intelligence can influence the level of organizational commitment, including employee commitment. The objectives of this study are as follows: 1) Investigating the impact of self-leadership on the emotional intelligence of public junior high school teachers in Bengkulu City. 2) Examining the effect of emotional intelligence on the organizational commitment of public junior high school teachers in Bengkulu City. 3) Examine the effect of self-leadership through the mediation of emotional intelligence on organizational commitment in public junior high school teachers in Bengkulu City. The conclusions of this study are as follows: 1) There is a significant influence between self-leadership on emotional intelligence. 2) There is a positive and significant relationship between emotional intelligence and organizational commitment. 3) There is a significant influence between self-leadership on organizational commitment with the mediation of emotional intelligence.